Affective Arrangements. (January 2019) - Slaby, Jan; Mühlhoff, Rainer; Wüschner, Philipp
We introduce the working concept of "affective arrangement." This concept is the centerpiece of a perspective on situated affectivity that emphasizes relationality, dynamics, and performativity. Our proposal relates to work in cultural studies and continental philosophy in the Spinoza–Deleuze lineage, yet it is equally geared to the terms of recent work in the philosophy of emotion. Our aim is to devise a framework that can help flesh out how affectivity unfolds dynamically in a relational setting by which it is at the same time modulated in recurring ways. With this orientation, this article contributes to the interdisciplinary study of situated affectivity and to the theoretical and conceptual unification of distinct strands of research from several disciplines.